PEMETAAN PENDIDIKAN KEAGAMAAN - Abdul Kadir M (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This writing is a research conclusion, that was conducted at severalplaces. They are Manado, Ternate, Jayapura, Makassar, Ambon, Palu,Samarinda, Mamuju, and Kendari. Data was collected using interviewand questioner. Data was analyzed using qualitative description.This study indicates that (1) local government and society support toIslamic school is very good; (2) organization of school is conducted byparticipative; (3) This schools output is very good